The effect of 22.5 kHz low‐frequency contact ultrasound debridement (LFCUD) on lower extremity wound healing for a vascular surgery population: A randomised controlled trial. Issue 3 (15th January 2018) - Murphy, Christine Anne; Houghton, Pamela; Brandys, Tim; Rose, Gregory; Bryant, Dianne
Abstract : The aim of this study was to compare changes in wound size and appearance and health complication rates in patients with vasculopathy and lower‐extremity wounds treated with or without low‐frequency contact ultrasound debridement (LFCUD) This study was a randomised controlled trial. The study was conducted in a vascular surgery service, including outpatient wound clinic and inpatient ward, in a tertiary care academic centre. In total, 70 patients with vasculopathy and lower‐extremity wounds of mixed aetiology were enrolled in the trial; 68 completed the study. Patients were randomised to receive LFCUD plus usual care ( n = 33) or usual care ( n = 37) at 4 weekly visits, and were followed thereafter for up to 12 wk. The main outcome measures included closed wounds, change in wound surface area (WSA), and wound appearance by the revised Photographic Wound Assessment Tool (revPWAT). After 4 weekly LFCUD treatments, patients in the LFCUD group had significantly better wound appearance (total revPWAT score) compared with the control group treated only with usual care ( P = <0.05). LFCUD‐treated wounds also had a significant reduction in WSA over 4 wk that was not found in the UC group. LFCUD treatment was also associated with a greater number of healed wounds, odds ratio 5.00 (95% CI 1.24‐20.25), and fewer instances of wound deterioration. Weekly LFCUD applications to patients with significant vasculopathy resulted in superior healing outcomes when compared with current usual wound care practice.